Corporate Governance Practices, Capital Structure And Their Impact On Firm Performance: A Study On Sri Lankan Listed Manufacturing Companies. - Velnampy, T.; Nimalthasan, P. (My University, 2013)
Purpose: Corporate governance is about putting in place the structure, processes and mechanism that ensure that the firm is being directed and managed in a way that enhances long term share holder value through accountability of managers and enhancing organizational performance. Corporate governance refers to a set of rules and incentives by which the management of a company is directed and controlled. Hence good corporate governance and capital structure maximizes the profitability and long term value of the firm for shareholders. There is a great awareness among the researchers to carry out the researches in “corporate governance’. Very little researches on “corporate governance” are available in Sri Lanka and need to be empowered companies to pay a special attention on corporate governance. The main objective of this study is to examine the relationship between corporate governance practices, capital structure and firm performance in listed manufacturing firms in Sri Lanka. Design: In a way, the present study is initiated on “corporate governance practices, capital structure and firm performance “with the samples of 25 manufacturing companies using the data representing the periods of 2008 – 2012. Leadership structure, board committee, board meeting, board size, board composition, were used as the determinants of corporate governance practices whereas debt equity ratio (DER) were used as the measures of capital structure and return on equity (ROE) and return on assets (ROA) were used as the measures of firm performance. The statistical tests were used includes: descriptive statistics, correlation and regression analyses. Findings: The study found that determinants of corporate governance are not correlated to the capital structure and firm performance measures of the organization. Regression model showed that corporate governance don’t affect companies’ DER, ROE and ROA. Further recommendations are also put forwarded in the research. Research Limitations/Implications: The study only used data from the 2008-2012 annual reports. However, the findings have highlighted the effects of corporate governance of the performance and capital structure. Originality/Value: The study contributes to literature in Sri Lanka. Furthermore, the finding of the paper can be considered as helpful for managers and users that are anxious to develop financial description quality and practices of corporate governance.
Keywords: Corporate Governance; Firm Performance; Capital Structure; Leadership Structure; Board Committee; Board Meeting; Board Size; Board Composition; Sri Lanka.